2000
DOI: 10.1097/00000478-200004000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Androgen Receptor and Prostatic Specific Markers in Salivary Duct Carcinoma

Abstract: Salivary duct carcinoma (SDC) is an uncommon, pathologically distinct entity characterized by its morphologic resemblance to ductal carcinoma of the breast and highly aggressive behavior. Approximately two thirds of patients die within 4 years of initial diagnosis despite aggressive, combined surgical resection and radiotherapy. Review of the literature indicates that androgen receptor (AR), a marker frequently detected in prostatic carcinoma, is expressed in over 90% of SDCs, whereas two common breast carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
102
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(108 citation statements)
references
References 43 publications
6
102
0
Order By: Relevance
“…Oddly, 58% of SDC also stain for prostatic acid phosphatase and 17% for prostate specific antigen. In addition, roughly 90% of SDC bear androgen receptors by immunohistochemistry, which may prove to be a fruitful target for therapeutic hormonal intervention (98).…”
Section: Salivary Duct Carcinomamentioning
confidence: 99%
“…Oddly, 58% of SDC also stain for prostatic acid phosphatase and 17% for prostate specific antigen. In addition, roughly 90% of SDC bear androgen receptors by immunohistochemistry, which may prove to be a fruitful target for therapeutic hormonal intervention (98).…”
Section: Salivary Duct Carcinomamentioning
confidence: 99%
“…High expression of androgen receptor has led to case reports describing responses to androgen deprivation therapy 5 . A potentially receptorindependent response to tamoxifen has also been demonstrated; however, more prospective data are needed to establish a role for hormonal therapy 6 .…”
Section: Discussionmentioning
confidence: 99%
“…AR mediates the effect of androgen by binding to specific DNA sequences and influences the transcription and translation of various genes (20,21). Fan et al, (22,23) suggested that AR may have a role in the pathogenesis of salivary duct carcinoma through the mediation of an epidermal growth factor receptor and transforming growth factor-α autocrine pathway similar to that seen in prostatic carcinoma. Nasser et al, (24) showed negative reactivity to androgen receptor in benign gland tumors, but positive reactivity was detected in two of ten mucoepidermoid carcinomas, two of ten adenoid cystic carcinomas, and most cases of salivary duct carcinoma.…”
Section: Discussionmentioning
confidence: 99%